Multifunctional boreholes in the scope of drought mitigation and its influence on children's school attendance and on the gender relations of households in the districts of Chigubo and Mapai in the province of Gaza in Mozambique (Research, Society and Development, 2022)
In Mozambique most of the population still lives in rural areas. To improve the lives of these populations, it is essential that the government of Mozambique design and implement rural development plans. In this context and for the purpose of the research, all households in the districts of Chigubo and Mapai that benefit from the multifunctional water wells were taken as the target population of the study, based on a sample of 118 households calculated based on statistical formulas. This is an exploratory descriptive research with a qualitative and quantitative approach, with the main objective of diagnosing gender relations (power relations - social division of labor, participation, leadership and empowerment of women and youth). From the results obtained in the districts of Chigubo and Mapai, about 58.54% of the constituents of the households are female and 41.46% are male. According to the respondents, what makes there are more women than men is the cultural aspect related to the division of labor, participation of members in water collection, and gender issues) in the areas where the boreholes are implanted. The holes brought benefits as they opened space for men and women to enjoy the same opportunities in terms of occupation and leadership. It also brought benefits in terms of shortening the distance, improving water quality, sharing water for livestock and human consumption.